DIGITAL LITERACY AND LINGUISTIC POLITENESS AMONG ADOLESCENTS IN ACEH TAMIANG - Nucifera, Prima; Saputra, Nizar; Yakob, Muhammad (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
This study examines the impact of digital technology on language politeness among teenagers in Aceh Tamiang Regency, highlighting the dual effects of technology and the need for digital literacy. The objectives are twofold: (1) to explore the influence of digital literacy on language politeness among teenagers and (2) to identify the principles of language politeness observed in their interactions. Employing a qualitative approach with descriptive methods, the research was conducted in Seruway and Kejuruan Muda subdistricts. The subjects, aged 12 to 24 years, were selected based on WHO's classification of teenagers and proportional random sampling techniques. Data were derived from the speech of teenagers, collected through observation using a Non-Participant Observation Technique. Analysis involved (1) observing and monitoring relevant speech, (2) recording and noting language use, (3) classifying speech into categories of direct and indirect politeness, and (4) analyzing the classified data. Findings indicate that digital literacy plays a significant role in promoting polite language use among teenagers. It helps counter the growing use of impolite expressions, which can create negative communication habits and risk offending others. This study underscores the importance of digital literacy in fostering respectful and effective communication among the youth in a technologically driven era.